Strategi Pengurusan Badan Kebudayaan Dan Kesenian Setia Budi Dalam Memelihara Tarian Kuda Kepang Di Batu Pahat, Johor - Siti Nadiatul Najwa, Binti Osman (Universiti Malaysia Sarawak (UNIMAS), 2017)
The study aims to examine the strategy management of the Badan Kebudayaan dan Kesenian Setia Budi in maintaining kuda kepang dance in Batu Pahat, Johor. In this study, qualitative method was used to analysis the interview data. The importance of this research is to determine strategies management used by Badan Kebudayaan dan Kesenian Setia Budi to maintain kuda kepang dance in Batu Pahat, Johor.